2019
DOI: 10.4236/jss.2019.71014
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Impact of Corporate Social Responsibility Reputation on Financial Performance—Based on Listed Company Data

Abstract: With the improvement of living conditions, more and more people have begun to pay attention to environmental safety and social responsibility issues. The market's growing resistance to irresponsible companies may be that these companies are not aware of the seriousness of the consequences of their consequences on corporate finances. Facing the increasingly harsh product safety environment in recent years, people are increasingly focusing on the pursuit of quality products. With the development of the global co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 2 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…‫ﻋﻠﻰ‬ ‫اﻟشر�ﺎت‬ ‫ﻤن‬ ‫اﻟكثیر‬ ‫ﻓﺈن‬ ‫اﻟشر�ﺎت،‬ ‫أداء‬ ‫ﻋﻠﻰ‬ ‫اﻻﺠتمﺎع�ﺔ‬ ‫اﻫتمﺎﻤﻬﺎ‬ ‫ﻤن‬ ‫ادت‬ ‫ز‬ ‫ة،‬ ‫�بیر‬ ‫أم‬ ‫ة‬ ‫ﺼﻐیر‬ ‫أﻛﺎﻨت‬ ً ‫اء‬ ‫ﺴو‬ ‫اﻟﻌﺎﻟم،‬ ‫ﻤستوى‬ ‫اﻻﺠتمﺎع�ﺔ‬ ‫اﻟمسؤوﻟ�ﺔ‬ ‫أﺼ�حت‬ ‫ﺤیث‬ ‫اﻻﺠتمﺎع�ﺔ،‬ ‫�ﺎﻟمسؤوﻟ�ﺔ‬ ‫وﻟ‬ ‫ة‬ ‫ﻀرور‬ ‫اﺴتثنﺎء‬ ‫ﺒﻼ‬ ‫اﻟشر�ﺎت‬ ‫ﻟجم�ﻊ‬ ً ‫ا‬ ‫ﺨ�ﺎر‬ ‫�س‬ (Grant, 2008) . (Carroll,1999;Simpson and Kohers, 2002;Orlitzky et al, 2003;Roman et al, 2006;Supriti and Damoder, 2010;Yigit and Mukhtar, 2017;Mingming, Xiaodan and Jerry, 2017;Shafat and Nasir, 2018;Obafemi, Oluwabunmi and Collins, 2018;Pang and Yuan, 2019;Gregor et al, 2019) ‫وﺠود‬ ‫إﻟﻰ‬ ‫أﺸﺎر‬ ‫اﻵﺨر‬ ‫اﻟ�ﻌض‬ ‫و‬ ، ‫اﻟمﺎﻟﻲ‬ ‫أداﺌﻬﺎ‬ ‫و‬ ‫ﻟﻠشر�ﺔ‬ ‫اﻻﺠتمﺎع�ﺔ‬ ‫اﻟمسؤوﻟ�ﺔ‬ ‫ﺒین‬ ‫ﺴﻠب�ﺔ‬ ‫ﻋﻼﻗﺔ‬ (Heli, Jaepil and Jiatao, 2008;Georgeta and Florinita, 2013;Hirigoyen and Poulain, 2015;Tianjiao and Xiang, 2019) ‫اﻟمسؤوﻟ�ﺔ‬ ‫ﺒین‬ ‫ﻋﻼﻗﺔ‬ ‫وﺠود‬ ‫ﻋدم‬ ‫آﺨرون‬ ‫ﯿرى‬ ‫ﺒینمﺎ‬ ، ‫اﻟمﺎﻟﻲ‬ ‫أداﺌﻬﺎ‬ ‫و‬ ‫ﻟﻠشر�ﺔ‬ ‫اﻻﺠتمﺎع�ﺔ‬ (Mc Williams and Siegel, 2001;Meher and Farah, 2007;Linthicum, Reitenga and Sanchez, 2010;Kwang-Ho et al, 2018;Tanveer et al, 2018) .…”
mentioning
confidence: 99%
“…‫ﻋﻠﻰ‬ ‫اﻟشر�ﺎت‬ ‫ﻤن‬ ‫اﻟكثیر‬ ‫ﻓﺈن‬ ‫اﻟشر�ﺎت،‬ ‫أداء‬ ‫ﻋﻠﻰ‬ ‫اﻻﺠتمﺎع�ﺔ‬ ‫اﻫتمﺎﻤﻬﺎ‬ ‫ﻤن‬ ‫ادت‬ ‫ز‬ ‫ة،‬ ‫�بیر‬ ‫أم‬ ‫ة‬ ‫ﺼﻐیر‬ ‫أﻛﺎﻨت‬ ً ‫اء‬ ‫ﺴو‬ ‫اﻟﻌﺎﻟم،‬ ‫ﻤستوى‬ ‫اﻻﺠتمﺎع�ﺔ‬ ‫اﻟمسؤوﻟ�ﺔ‬ ‫أﺼ�حت‬ ‫ﺤیث‬ ‫اﻻﺠتمﺎع�ﺔ،‬ ‫�ﺎﻟمسؤوﻟ�ﺔ‬ ‫وﻟ‬ ‫ة‬ ‫ﻀرور‬ ‫اﺴتثنﺎء‬ ‫ﺒﻼ‬ ‫اﻟشر�ﺎت‬ ‫ﻟجم�ﻊ‬ ً ‫ا‬ ‫ﺨ�ﺎر‬ ‫�س‬ (Grant, 2008) . (Carroll,1999;Simpson and Kohers, 2002;Orlitzky et al, 2003;Roman et al, 2006;Supriti and Damoder, 2010;Yigit and Mukhtar, 2017;Mingming, Xiaodan and Jerry, 2017;Shafat and Nasir, 2018;Obafemi, Oluwabunmi and Collins, 2018;Pang and Yuan, 2019;Gregor et al, 2019) ‫وﺠود‬ ‫إﻟﻰ‬ ‫أﺸﺎر‬ ‫اﻵﺨر‬ ‫اﻟ�ﻌض‬ ‫و‬ ، ‫اﻟمﺎﻟﻲ‬ ‫أداﺌﻬﺎ‬ ‫و‬ ‫ﻟﻠشر�ﺔ‬ ‫اﻻﺠتمﺎع�ﺔ‬ ‫اﻟمسؤوﻟ�ﺔ‬ ‫ﺒین‬ ‫ﺴﻠب�ﺔ‬ ‫ﻋﻼﻗﺔ‬ (Heli, Jaepil and Jiatao, 2008;Georgeta and Florinita, 2013;Hirigoyen and Poulain, 2015;Tianjiao and Xiang, 2019) ‫اﻟمسؤوﻟ�ﺔ‬ ‫ﺒین‬ ‫ﻋﻼﻗﺔ‬ ‫وﺠود‬ ‫ﻋدم‬ ‫آﺨرون‬ ‫ﯿرى‬ ‫ﺒینمﺎ‬ ، ‫اﻟمﺎﻟﻲ‬ ‫أداﺌﻬﺎ‬ ‫و‬ ‫ﻟﻠشر�ﺔ‬ ‫اﻻﺠتمﺎع�ﺔ‬ (Mc Williams and Siegel, 2001;Meher and Farah, 2007;Linthicum, Reitenga and Sanchez, 2010;Kwang-Ho et al, 2018;Tanveer et al, 2018) .…”
mentioning
confidence: 99%
“…These variables have been adopted because social responsibility is more substantially linked to economic and business motives than altruistic or moral motives, as certain studies have demonstrated (e.g., Fernández-Gago and Martínez-Campillo, 2008;Crespo-Razeg, 2010). For example, Wang (2011) has observed the implementation of social responsibility improving corporate image, positively impacting stock returns for Taiwanese enterprises, and the findings of Pang and Yuan (2019) positively correlate social responsibility and financial performance. Also, it is needed and relevant the research on the relationship of corporate social responsibility and economic performance at regional level (Chen, Zhang and Hao, 2019).…”
Section: Introductionmentioning
confidence: 99%